Socioeconomic and cultural impacts of water scarcity on rural communities in Pakistan’s Pothwar Plateau - Zubair, Asim; Fatima, Sonia; Rashid, Muhammad (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
The Pothwar Plateau in Pakistan, encompassing the districts of Chakwal, Attock, and Jhelum, is experiencing severe water scarcity, which has a significant socioeconomic impact on the nearby rural population that primarily depends on rain-fed agriculture. Through semi-structured interviews, focus groups, and field observations, this study employed a qualitative research methodology to investigate the impact of water shortages on household income, agricultural production, migratory trends, health, education, and social stability. According to the findings, crop yields have decreased significantly due to unpredictable rainfall and groundwater depletion, prompting many farmers to abandon farming altogether or switch to low-value crops. Rural-urban migration has been exacerbated by the decline in agricultural revenue, particularly the loss of young male labour, which has intensified the economic and social constraints on families left behind, especially women. Competition for water supplies has also led to disputes within communities and the eventual breakdown of traditional water-sharing systems. The poverty cycle has been made worse by declining health and education investment as a result of family financial hardships. Although local communities have attempted to address water shortages through conventional means, their efforts have been constrained by a lack of infrastructure investment and regulatory support. To increase water use efficiency and social resilience, the Pothwar region urgently needs an integrated water resources management (IWRM) strategy that combines contemporary water-saving technologies (like drip irrigation and rainwater harvesting) with community participatory governance, according to the study. The study's findings provide valuable insights for policymakers in Pakistan and other regions affected by drought, supporting the pursuit of sustainable development and equitable water distribution.